The Influence Of Work Motivation And Work Discipline On The Performance Of Non-PNS Employees Of The Ciamis Regency Manpower Service : - Supratama, Moh. Ramdhansyah; Rahwana, Kusuma Agdhi; Patimah, Titin (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
This research aims to determine the influence of work motivation and work discipline on the performance of non-civil servant employees at the Ciamis Regency Manpower Service. The method used was quantitative with a research sample of 35 respondents. The data used are primary and secondary data. The analytical tool used in this research is multiple linear regression analysis using SPSS version 25. Based on the research results, it shows that Work Motivation and Work Discipline simultaneously have a positive and significant effect on Employee Performance. Work motivation partially has a significant effect on employee performance. Partial Work Discipline does not have a significant effect on Employee Performance.